Soliton mode-locked thulium-doped fiber laser with cobalt oxide saturable absorber - Ahmad, Harith; Samion, Muhamad Zharif; Yusoff, Norazriena (Elsevier, 2018)
In this work, we propose and demonstrate a mode-locked thulium doped fiber laser (TDFL) with an integrated cobalt oxide (Co3O4) saturable absorber (SA). The SA is fabricated by suspending Co3O4 nanosheets in a polymer film before being secured between two fiber ferules. The laser operates in the anomalous dispersion regime, confirmed by the Kelly sidebands observed in the obtained optical spectrum. Mode-locking operation is obtained at a low threshold pump power of 77.32 mW, with further optimizations made using a polarization controller The laser generates pulses with a repetition rate of 11.36 MHz and a pulse width of 1.39 ps. The generated pulses are highly stable, with a high signal-to-noise ratio of 46.00 dB and minimum power fluctuations indicating a long-term stability. This work demonstrates a simple and a low-cost laser that would have potential applications for operation near the 2.0-µm region, especially for medical applications.